Application of Polarization and Depolarization Current Measurement for Rotating Machine Insulation Analysis - Norasage Pattanadech; P. Nimsanong; Tehneht Worthong (2021 3rd International Conference on High Voltage Engineering and Power Systems (ICHVEPS), 2021)
Rotating machine is a vital asset of the power plants. For the motors and generators in service, the stator winding insulation is generally operated under thermal, electrical, ambient, and mechanical stresses. The combination of these stresses causes insulation degradation that can lead to early aging or severe damage and, finally, the failure of such machines. The failure of rotating machines may result in immense financial loss and other aspects. Polarization and depolarization current (PDC) measurement has been introduced as one of the time-domain dielectric spectroscopy test techniques applied for insulation condition testing. This paper represents the application of PDC measurement to evaluate the insulation for the stator bars/coil insulation experienced with various kinds of stresses. Moreover, the PDC field test of generators and high voltage motors used in the power plants is introduced. From the experiments, the dielectric parameters obtained from PDC measurements are clearly useful parameters to evaluate the electrical insulation of such rotating machines.
Keywords: High voltage insulation and dielectric phenomena; Power Transformer Diagnostics and Insulation; Lightning and Electromagnetic Phenomena